Callus induction and development of suspension cell culture of Malaysian upland rice cultivar Panderas - P. Rajadran, Nisha (2015)
The aim of the study is to evaluate the effect of amino acid (tryptophan and glutamine) on the callus induction and to develop suspension cell culture protocol for Malaysian upland rice, Panderas cultivar. The research revealed that callus induction varied depend on amino acid tested. In callus induction study, dehusked Panderas mature seeds were placed on MSB5 medium supplemented with 3mg/L 2,4-D and 2mg/L NAA with four different concentrations of tryptophan and glutamine separately. After three weeks in culture, inclusion of tryptophan showed positive effect on percentage of callus induction and fresh weight. It was observed that the optimum concentration of tryptophan was 25mg/L with 96.67% of callus induction and 73.33mg of average fresh weight. At week six, the average fresh weight of callus induced on MSB5 media supplemented with 25mg/L tryptophan was increased to three fold (215mg). Treatment without amino acids (control) showed similar callus percentage (96.67%) and three times increased in fresh weight after six weeks. However addition of 50mg/L glutamine alone showed lower percentage of callus induction and fresh weight compare to tryptophan and control treatment. The callus proliferation resulted in yellowish colour and nodular appearance showing embryogenic potential. The embryogenic callus was then immersed in 1% Evans blue to validate the viability of cells. Five weeks old potential embryogenic callus was then selected to initiate suspension cell culture. The N6 liquid medium supplemented with 3mg/L 2,4-D, 1mg/L kinetin and 0.005% pectinase resulted in higher fresh weight (1.84g) of suspension cells compared to without pectinase on day ten of incubation. This study concludes that tryptophan and glutamine did not show significant response on percentage of callus induction and fresh weight. Besides that inclusion of pectinase in suspension cell culture may increase fresh weight of suspension cell